Cloud information technology as a factor in business development - Ponomarova, Mariia; Harkusha, Olena O. (My University, 2022)
The introduction of modern technologies in common, and cloud software service, in particular, allow to optimize the business processes of the enterprise, reduce resource costs, increase productivity, ensure the growth of enterprise profits and speed up the transition to a new stage of its development. Впровадження сучасних технологій, зокрема хмарного програмного сервісу, дозволяє оптимізувати бізнес-процеси підприємства, зменшити витрати ресурсів, підвищити продуктивність, забезпечити зростання прибутку підприємства та прискорити перехід на новий етап його розвитку.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; information technologies; сloud computing; security; software; інформаційні технології; хмарні обчислення; безпека; програмне забезпечення